Isomorphism and compliance: exploring the impact on integrated reporting practices - Abeywardana, N.L.E.; Azam, S.M. Ferdous (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study delved deeper into the impact of isomorphic pressure on adopting integrated reporting practices through the lenses of the Institutional Theory and the Gibbin’s Model, focusing on the mediating role of disclosure position in the context of an emerging economy. The study employed a survey research design using a sequential mixed-method approach. Quantitative data were collected using a questionnaire distributed to public listed companies in Sri Lanka, which produced 126 usable responses for the analysis. Qualitative data were used to explore quantitative findings. The quantitative findings revealed that isomorphic pressure and disclosure position positively influenced the adopting of integrated reporting practices. Concurrently, the research lends credence to the role of disclosure position as a mediator in this relationship. The case of isomorphic influence and disclosure stance was strengthened by the qualitative findings used to explore quantitative findings. This study will aid regulatory bodies, professional accounting bodies, and businesses in raising awareness and supporting widespread adoption. From the Institutional Theory and Gibbin’s Model perspectives, this was the first study to analyze the collective influence of coercive, mimetic, and normative isomorphisms adopting integrated reporting practices and how the disclosure position mediated this relationship.